Discriminação cromática em adultos insones - Almeida, Natália Leandro de (2021)
Insomnia is a sleep disorder characterized by difficulty in initiating or maintaining sleep, accompanied by a constant feeling of insufficient and unrestorative sleep, which can compromise general health and quality of life, in addition to affecting psychosocial and psychological processes. neurobiological. The aim of this study was to investigate the color discrimination of adult insomniac volunteers. Thirty-one volunteers participated in this study, being: 16 in the Control Group (CG; 25.38 ± 4.1 years of age) and 15 in the Study Group (EG; 27.6 ± 4.9 years of age). The Insomnia Severity Index (ISI), Athens Insomnia Scale, Pittsburgh Sleep Quality Index (PSQI), Beck Depression and Anxiety Inventories (BAI and BDI) and the Morning and Evening Questionnaire were used as instruments. (MEQ). All participants had normal or normal-to-corrected (20/20) visual acuity and no dyschromatopsia was observed by the Ishihara test. The study was carried out in two stages, in the first stage there was a screening of signs for insomnia disorder through an online questionnaire and, in another stage, subjective behavioral measures of sleep and color discrimination were performed using the Lanthony D 15d. The results showed no significant differences between age (p = 0.211) and level of education (p = 0.265) between the groups. Nonparametric data analysis for independent Mann Whitney groups also did not show significant differences for the Color Confusion Index (ICC) [U = 74.00, p = 0.069] and S-Index [U = 110.5, p = 0.707]. This study did not point out significant differences between insomnia and the color discrimination test. However, more research is suggested that use the ordering of hues by means of behavioral and electrophysiological tests in insomniac patients and other sleep disorders.